Corrective Feedback Towards Student’s English Writing of Hospital Administration Students at STIKES Baptist Hospital Kediri - febrijanto, yoyok (Kirana Publisher (KNPub), 2023)
Administration students at STIKES Baptist Hospital Kediri using descriptive qualitative approach. The subjects was 9 students of second semester. Collecting data about corrective feedback used questionnaire and interview about students’ response in terms of attitude. Analysis data based on three concurrent flows of activities: data reduction, data display, and conclusion. The result showed that the teacher gave direct corrective feedback in students’ English writing by circling the students’ errors and providing the correct answer in grammar, spelling, punctuation, capitalization, preposition, article and content. The data from questionnaire for students’ attitude showed most of students agreed that the teacher should point out grammar errors. The students have positive responses by remembering their grammar mistakes and feel more motivated to go on learning when the teacher corrects their error in writing. They answered that they will revise their writing if their errors are corrected by the teacher. It can be concluded that most of the students have positive attitude to teacher’s corrective feedback.